3D printing of internal transparent products

By selecting the appropriate amorphous thermoplastic polymer matrix and controlling the internal temperature, the polymer chains are allowed to flow and entangle at high temperatures, solving the problem of difficult internal clarity and low haze of transparent 3D printing components in the prior art, and achieving efficient, transparent and dense 3D printing components production.

CN114375247BActive Publication Date: 2025-03-11ARKEMA FRANCE SA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080026286.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-03-27
Publication Date
2025-03-11
Estimated Expiration
2040-03-27

AI Technical Summary

Technical Problem

The prior art is difficult to maintain internal clarity and low haze while efficiently producing transparent 3D printed components, especially at thicker layers and faster printing speeds.

Method used

Layer lines and bubbles are reduced or eliminated by selecting an amorphous thermoplastic polymer matrix with an appropriate glass transition temperature (Tg) and additives and controlling the internal temperature during the printing process so as to be at least 25°C above the material Tg to allow flow of polymer chains and interlayer entanglement.

Benefits of technology

3D printed parts for the production of amorphous thermoplastic polymers at high internal temperatures are achieved, with high transparency and low haze, with a density of nearly 100%, and with the ability to maintain clarity at thicker layers and faster printing speeds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114375247B_ABST
    Figure CN114375247B_ABST
Patent Text Reader

Abstract

The present invention relates to a material extrusion additive manufacturing method for producing clear internal transparent parts composed of amorphous thermoplastic polymer layers at least 0.1 mm thick. The present invention also relates to internal clear parts made by the method, whose internal haze is less than 25%, less than 15%, less than 10% or even less than 5%. The method produces printed dots or lines of amorphous thermoplastic polymers that can be maintained at high internal temperatures for a long enough time so that the polymer chains in each layer can move and flow, allowing sufficient interlayer chain entanglement to reduce and eliminate layer lines. The density of the final part is close to 100%, and voids are eliminated. The resulting printed article has very high internal clarity and can have a haze of less than 5%.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to a material extrusion additive manufacturing method for producing clear internal transparent parts composed of amorphous thermoplastic polymer layers at least 0.1 mm thick. The present invention also relates to internal clear parts made by the method, whose internal haze is less than 25%, less than 15%, less than 10% or even less than 5%. The method produces printed dots or lines of amorphous thermoplastic polymers that can be maintained at high internal temperatures for a long enough time so that the polymer chains in each layer can move and flow, allowing sufficient interlayer chain entanglement to reduce and eliminate layer lines. The density of the final part is close to 100%, and voids are eliminated. The resulting printed article has very high internal clarity and can have a haze of less than 5%. Background of the Invention

[0003] Equipment advances and price reductions have made 3D printing a fast, simple, and often inexpensive way to prototype and manufacture custom end-use parts for widespread use in homes, schools, and industry. Specifically, material extrusion additive manufacturing 3D printing (also known as fused filament fabrication or fused deposition molding) has become the tool of choice for direct consumer use, mass production, and rapid thermoplastic prototyping because it is the easiest to operate, produces the least waste, and offers the shortest turnaround time for 3D printing technology.

[0004] Many materials have been used to prepare 3-D printed articles for various end uses, from chocolate to collagen. Thermoplastic materials are particularly suitable for use with material additive extrusion printers. Unfortunately, few thermoplastic materials offer good mechanical properties, transparency, and are easy to print.

[0005] Polylactic acid (PLA) is widely used in desktop home printers because it prints well with very low warping. Unfortunately, it has a low service temperature and poor chemical stability; it will yellow (degrade) during printing when not stained with dyes or pigments. Acrylonitrile butadiene styrene (ABS) is a more stable and commonly used "engineering" thermoplastic for 3D printing, and has a higher service temperature - but it exhibits higher warping during printing, is not transparent, and has a printed elongation at break of less than 6%. Polyethylene terephthalate glycol (PETG) and other copolyesters have become very popular additions to the 3D printing space due to their higher service temperatures and similar stability to ABS and improved printability - but they have lower hardness and scratch resistance.

[0006] Acrylic polymers are known for their clarity, shiny colors, surface gloss, image depth, and weather resistance. They have a similar service temperature to ABS. Unfortunately, the brittleness associated with acrylic polymers makes them unsuitable for making filaments for extrusion additive 3-D printing.

[0007] The ability to 3D print transparent parts using thermoplastics has long been a goal of the 3D printing community. However, despite the use of transparent materials, the behavior of material extrusion-based 3D printing often adds a large number of polymer layer-air and / or polymer line-air interfaces, making the printed parts hazy and opaque. The layer / line interfaces on the outer surface can be reduced by surface polishing or coating, but the inner layer / line interfaces are not easily removed.

[0008] Recently, it has been reported that "transparent" parts have been 3D printed using ABS, copolyester, and PETG filaments. Typically, the parts are very small and appear yellow, bubbly, or cloudy. In addition, parts are typically printed at very low layer heights (0.05mm) at slow speeds, so parts take a long time to produce. At thicker layer heights or faster speeds, the resulting parts no longer appear transparent. Acrylic filaments have also not been previously demonstrated, possibly due to the difficulty of processing traditional acrylic filaments in material extrusion 3D printers.

[0009] It is necessary to 3D print transparent articles with an actual layer height of at least 0.1 mm while maintaining an extrusion speed of at least 15 mm / s. It is preferred to increase the layer height to shorten the printing time, because extrusion speeds greater than 50 mm / s tend to result in very inaccurate printing. Surprisingly, it has now been found that by appropriately selecting the composition, Tg, additives and optimized printing processing conditions (minimum fan / active cooling, print bed temperature and build chamber coordinated with the material's transition temperature, and setting the layer height), internal transparent polymer parts can be produced at normal layer heights with a haze of less than 20%, preferably less than 15%, preferably less than 10% and as low as less than 5%, without slowing down the printing speed. Select materials and printing conditions so that each printed polymer point is maintained at a temperature of at least 25°C, more preferably 45°C, 55°C or even higher than the material Tg for at least 10 minutes, 15 minutes or even 20 minutes, so that the polymer can move and flow, produce interlayer entanglements of polymer chains, reduce or even eliminate layer lines and bubbles, thereby providing very high internal transparency of even less than 10% and a haze of 5%.

[0010] In addition to providing high definition in 3D printed parts due to intermingling of different layers, the same layer intermingling increases the Z-direction strength in the 3D printed article and produces parts with minimal internal stress. Moreover, by producing parts without any internal layer lines or defects, the parts are even more suitable for non-clear applications such as light diffusers and mechanically demanding parts. In this part, color transmission is also improved. Summary of the invention

[0011] The present invention relates to an additive manufacturing material extrusion printing method, the method comprising the following steps:

[0012] a) selecting an amorphous thermoplastic polymer matrix composition, the composition having a certain Tg as a whole;

[0013] b) selecting conditions sufficient to provide an internal temperature of the composition wherein the bulk Tg of the composition is at least 25°C below the internal temperature, more preferably at least 30°C below, more preferably at least 40°C below, even more preferably at least 50°C below, and even 60°C below;

[0014] c) 3D printing the amorphous thermoplastic polymer to form an article,

[0015] The temperature difference between the Tg of the amorphous thermoplastic polymer and the internal temperature is maintained for at least 5 minutes after printing, preferably for at least 10 minutes, more preferably for at least 15 minutes, and most preferably for at least 20 minutes.

[0016] In a second aspect of the invention, the material extrusion method comprises selecting conditions to provide a desired internal temperature selected from one or more of the following:

[0017] a) selecting a build plate temperature that is higher than the Tg of the amorphous thermoplastic polymer composition, more preferably at least 10°C higher than the Tg of the amorphous thermoplastic polymer composition, most preferably at least 20°C higher. In another embodiment, the build plate temperature can also be expressed as a % higher than the Tg of the amorphous thermoplastic polymer composition - at least 10% higher than the amorphous thermoplastic polymer composition, preferably 10% to 50% higher, more preferably at least 20% higher, more preferably at least 30% higher, and even 40% higher than the Tg of the amorphous thermoplastic polymer;

[0018] b) selecting a heating chamber temperature that is at least 20°C, preferably at least 30°C, preferably at least 40°C and most preferably at least 50°C higher than the Tg of the composition;

[0019] c) Use radiant heating sources to supplement the heat during printing;

[0020] d) Little or no fans or active cooling;

[0021] e) Printing speed is 25 mm / s;

[0022] f) Using selected additives in the composition to lower the Tg of the composition, or to help maintain the composition at temperature for a longer period of time.

[0023] In a third aspect of the present invention, in the additive manufacturing method as described in any one of the preceding aspects, the amorphous thermoplastic polymer composition comprises a polymer selected from the group consisting of: including but not limited to (meth)acrylic polymers, copolyesters, polycarbonates, polyamides, polyhydroxyalkanoates, amorphous polyamides and poly(styrene-co-maleic anhydride).

[0024] In a fourth aspect of the invention, the additive manufacturing method as described in any of the preceding aspects comprises: the Tg of the amorphous thermoplastic polymer composition is less than 160°C, preferably less than 150°C, preferably less than 140°C, preferably less than 130°C, preferably less than 120°C, preferably less than 114°C, preferably less than 104°C, preferably less than 94°C, more preferably less than 80°C and most preferably less than 75°C.

[0025] In a fifth aspect of the present invention, the additive manufacturing method according to any one of the preceding aspects, wherein the amorphous thermoplastic polymer composition is selected from the group consisting of:

[0026] a) a copolymer having a desired Tg,

[0027] b) blends of polymers having a Tg greater than 140°C and low viscosity polymers,

[0028] c) Blends of polymers having a Tg greater than 140°C and additives capable of lowering the Tg or increasing the open time of the polymer composition, wherein the open time is the time required to allow continuous melting of polymer strands for merging and / or spooling.

[0029] In a sixth aspect of the present invention, the additive manufacturing method according to any one of the preceding aspects uses an amorphous thermoplastic polymer composition, which further comprises an impact modifier in an amount of 5 to 60 wt % based on the total composition weight.

[0030] In a seventh aspect of the present invention, the additive manufacturing method as described in any of the preceding aspects, wherein the temperature of the amorphous thermoplastic polymer composition is provided and / or maintained by one or more means selected from the group consisting of: a) low or no fan or active cooling, b) a heated print bed, c) a heated chamber, and d) a radiant heat source.

[0031] In an eighth aspect of the present invention, the additive manufacturing method as described in any of the preceding aspects produces a 3D printed article with a packing density of 99% or higher.

[0032] In a ninth aspect of the present invention, the additive manufacturing method as described in any one of the preceding aspects comprises: an amorphous thermoplastic polymer composition, wherein the amorphous thermoplastic polymer composition is an acrylic polymer.

[0033] In a tenth aspect of the present invention, in the additive manufacturing method as described in any one of the preceding aspects, the amorphous thermoplastic polymer composition is printed with a layer height of ≥0.05 mm, ≥0.1 mm, ≥0.2 mm, ≥0.3 mm, or ≥0.4 mm.

[0034] In another aspect of the present invention, an internally clear 3D printed article is formed, wherein the article is printed using a deposition layer thickness greater than or equal to 0.1 mm, preferably greater than or equal to 0.2 mm, preferably greater than or equal to 0.3 mm, preferably greater than or equal to 0.4 mm, and the internal haze is less than 25%, preferably less than 20%, preferably less than 10%, and preferably less than 5%.

[0035] In another aspect of the present invention, the 3D printed article comprises an acrylic composition, a copolyester, an amorphous polyamide, or a polycarbonate.

[0036] BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 : Schematic diagram showing the test used in Example 1.

[0038] Figure 2 and 3 : IR image of Example 3.

[0039] Figure 4 and 5 : The double extruded block of Example 4 is shown.

[0040] 6-11 show the rheological curves of the samples of Example 1.

[0041] Fig.12 and 13 This is a thermal image of the components of Example 6. DETAILED DESCRIPTION OF THE INVENTION

[0043] The present invention relates to a method for producing a clear internal transparent part from an amorphous thermoplastic polymer, which consists of a layer at least 0.1 mm thick. The present invention also relates to an internal clear part produced by this method, whose internal haze is less than 25%, less than 15%, less than 10% or even less than 5%.

[0044] All references cited are incorporated herein by reference. As used herein, percentages shall refer to weight percentages unless otherwise indicated. Molecular weights are weight average molecular weights determined by GPC. When the polymer contains some crosslinks, GPC cannot be used due to the insoluble polymer fraction, and the molecular weight of the soluble fraction / gel fraction or the soluble fraction after extraction from the gel is used.

[0045] "Copolymer" is used to refer to a polymer having two or more different monomer units. "Polymer" is used to refer to both homopolymers and copolymers. Polymers can be linear, branched, star-shaped, comb-shaped, block-shaped or any other structure. Polymers can be homogeneous, heterogeneous, and can have a gradient distribution of comonomer units.

[0046] (Meth)acrylic acid or (meth)acrylate refers to methacrylic acid and acrylic acid, or methacrylate and acrylate.

[0047] Tg is used as an alternative measurement of transition temperature, which is the temperature at which a material changes from a liquid to a solid state from a rheological perspective. The so-called transition temperature is the temperature at which the slope of the logarithm of viscosity versus temperature curve changes according to the Arrhenius equation, reflecting the change from liquid to solid properties. This transition point can be obtained by measuring the viscosity of the material under low shear from the melt phase to room temperature. A transition temperature of 10°C, preferably 20°C, even more preferably 25°C, 30°C lower than the internal temperature reached by the part during printing (about 135°C when printing on a 120°C heated print bed without a heating chamber and minimal fans) is required. The Tg of many acrylic materials is about 25°C lower than the transition temperature. In other words, the Tg of a material printed on a 120°C heated print bed at room temperature is preferably below 104°C, 94°C, 84°C and 75°C but above 60°C. If a heated chamber is used, the part will experience a higher internal temperature, so a material with a higher Tg can also be used, and similarly, if a hotter heated print bed is used, a material with a higher Tg can also be used. The glass transition temperature of a polymer is measured by DSC according to standard ASTM E1356.

[0048] The first G' / G" crossover temperature refers to the first temperature at which G' is greater than G" as measured by parallel plate rheology at low shear as the material goes from the melt to room temperature, where the storage modulus G' (i.e., elastic response) is greater than the loss modulus G" (i.e., viscous response). In general, the dynamic modulus is a measure of the viscoelastic properties of a material and is the storage modulus G' (i.e., elastic response) and the loss modulus G" (i.e., viscous response) of a polymer. The crossover temperature (G'=G") can serve as the onset of stiffening because at lower temperatures, the elastic modulus dominates over the viscous response. While not being bound by any theory, it is believed that a higher first G' / G" crossover temperature will allow the material to better retain its shape during a heat soak.

[0049] The clear processing range is defined as the temperature difference between the first G' / G" crossover temperature and the LS transition temperature. Characterizing this window as a reference for clear printing is particularly useful when the Tg of the printed material is not a direct surrogate parameter for the transition temperature and / or manipulation of the composition cannot be performed to use as a surrogate parameter.

[0050] Additive manufacturing or additive manufacturing methods as used herein refers to melt extrusion printing or deposition of molten thermoplastics. This method is also known as 3D printing.

[0051] Transmittance and haze were measured using a BYK-Gardner Haze-Gard machine according to ASTM D1003.

[0052] Several factors can be selected to provide material properties, construction time, and internal environmental conditions to allow polymer chains in each print layer dot / line to interact and entangle with polymer chains in adjacent print dots. These are discussed below:

[0053] Material composition

[0054] To obtain an overall lower Tg composition, one can a) select a polymer or copolymer with a desired Tg, b) blend a higher Tg polymer with a compatible low Tg, lower viscosity polymer, or c) blend a higher Tg polymer with an additive such as a plasticizer.

[0055] Polymer Matrix

[0056] The polymer matrix of the present invention is an amorphous polymer. Semi-crystalline and crystalline polymers contain crystalline regions, which are known to diffract light, resulting in increased haze. Available polymers of the present invention include, but are not limited to, (meth) acrylics, copolyesters, polycarbonates, and amorphous polyamides. The present invention is illustrated using (meth) acrylic polymers and amorphous polyamides, but those of ordinary skill in the art will be able to apply the present invention to other amorphous polymers using the description and examples provided herein. Although the matrix polymer preferably has a single polymer with a single Tg, polymer blends or even block copolymers with two or more Tgs may be used. In the case where the matrix has more than one polymer or block and has more than one Tg, the lower Tg will be referred to as the Tg of the matrix polymer in this article. It should be noted that this refers to the polymer matrix, rather than other polymer additives that may also be present in the composition, such as impact modifiers. The matrix polymer is the continuous phase of the composition.

[0057] As used herein, "acrylic polymers" are intended to include polymers, copolymers, and terpolymers formed from alkyl methacrylate and alkyl acrylate monomers and mixtures thereof. The alkyl methacrylate monomer is preferably methyl methacrylate, which may comprise 50 to 100% of the monomer mixture. 0 to 50% of other acrylate and methacrylate monomers or other ethylenically unsaturated monomers (including, but not limited to, styrene, α-methylstyrene, acrylonitrile) and low levels of crosslinking agents may also be present in the monomer mixture. Other methacrylate and acrylate monomers that may be used in the monomer mixture include, but are not limited to, methyl acrylate, ethyl acrylate and ethyl methacrylate, butyl acrylate and butyl methacrylate, isooctyl methacrylate and isooctyl acrylate, n-octyl acrylate, lauryl acrylate and lauryl methacrylate, stearyl acrylate and stearyl methacrylate, isobornyl acrylate and isobornyl methacrylate, methoxyethyl acrylate and methacrylate, 2-ethoxyethyl acrylate and methacrylate, isodecyl acrylate and methacrylate, tert-butyl cyclohexyl acrylate and tert-butyl methacrylate, tert-butyl methacrylate, The monomer mixture may be cyclohexanol ester, trimethylcyclohexyl acrylate and trimethylcyclohexyl methacrylate, methoxypolyethylene glycol methacrylate containing 2-11 ethylene glycol units and methoxypolyethylene glycol acrylate containing 2-11 ethylene glycol units, pentyloxyethyl acrylate and pentyloxyethyl methacrylate, alkoxylated phenol acrylate, ethoxylated phenyl acrylate and ethoxylated phenyl methacrylate, glycidyl methacrylate, tetrahydrofurfuryl acrylate and tetrahydrofurfuryl methacrylate, alkoxylated tetrahydrofurfuryl acrylate, cyclotrimethylolpropane dimethoxymethane (formal) acrylate, caprolactone acrylate, dimethylaminoethyl acrylate and dimethylaminoethyl methacrylate monomers. Alkyl (meth) acrylic acid (e.g., methacrylic acid) and acrylic acid or its C1-C8 ester may be used for the monomer mixture. Most preferably, the acrylic polymer is a monomer having 70-99.5 wt% of methyl methacrylate units and 0.5-30 wt% of one or more C 1-8 Copolymers of linear or branched alkyl acrylate units.

[0058] The weight average molecular weight of the acrylic polymer is 50,000 g / mol to 500,000 g / mol, preferably 55,000 g / mol to 300,000 g / mol, and preferably 75,000 g / mol to 200,000 g / mol. It has been found that using a lower weight average molecular weight acrylic polymer within this range increases the density of the material extruded additively printed article, increases transparency, and reduces warping.

[0059] Preferably, the acrylic polymer contains little or no very high molecular weight fraction of polymer and less than 5 wt % of the acrylic polymer, preferably less than 2 wt % of the acrylic polymer has a molecular weight greater than 500,000 g / mol.

[0060] In another embodiment, the acrylic polymer comprises a blend of two or more polymers described in the two embodiments above.

[0061] Acrylic polymers can be synthesized by any known method including, but not limited to, bulk polymerization, emulsion polymerization, solution polymerization, and suspension polymerization.

[0062] Acrylic copolymer:

[0063] The acrylic copolymer of the present invention has a Tg of less than 160°C, preferably less than 150°C, preferably less than 140°C, preferably less than 130°C, preferably less than 120°C, preferably less than 114°C, preferably less than 104°C, preferably less than 95°C, preferably less than 85°C and more preferably less than 75°C, and a Tg of greater than 50°C, preferably greater than 55°C and more preferably greater than 60°C.

[0064] In a preferred embodiment, at least 40 wt%, preferably at least 50 wt%, and most preferably at least 60 wt% of the monomer units in the acrylic copolymer are methyl methacrylate monomer units. The comonomer selected for the acrylic copolymer can be a (meth)acrylic monomer, a non-(meth)acrylic monomer, or a mixture thereof.

[0065] In a preferred embodiment, the acrylic copolymer comprises greater than 90 wt%, greater than 95 wt%, and most preferably 100 wt% acrylic monomer units. Low Tg acrylic monomers that can be copolymerized to reduce the copolymer Tg to a specified level include, but are not limited to, methyl acrylate, ethyl acrylate, butyl acrylate, ethylhexyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, hexyl methacrylate, n-octyl acrylate, lauryl methacrylate, and butyl methacrylate. These monomers are added in an amount sufficient to reduce the Tg to less than 95°C, less than 85°C, preferably less than 80°C, and more preferably less than 75°C, as is well known in the art, and Tg can be easily calculated using the Fox equation and can be measured by DSC. For example, a 70 wt% methyl methacrylate (MMA) / 30 wt% ethyl acrylate composition has a Tg of about 75°C.

[0066] Copolymers with lower Tg tend to have lower viscosities than polymers with higher Tg, although other factors (eg, molecular weight and branching) will also affect viscosity. Impact modifiers may be and preferably are added to the composition to provide a compromise between improving impact strength and increasing melt flow viscosity.

[0067] Although the acrylic composition of the present invention may not contain an impact modifier, in a preferred embodiment, in order to avoid excessive brittleness, the acrylic composition of the present invention contains one or more types of impact modifiers. Preferably, the acrylic composition contains an impact modifier in an amount of 5 to 60 weight %, preferably 9 to 40 weight %, and more preferably 20 to 35 weight %, based on the overall composition. As known in the art, the impact modifier can be any impact modifier that is compatible, miscible or semi-miscible with the acrylic composition. Useful impact modifiers include, but are not limited to: linear block copolymers and core-shell impact modifiers containing both a soft core and a hard core. In a preferred embodiment, the impact modifier has an acrylic block or an acrylic shell.

[0068] Without being bound by any particular theory, it is believed that impact modifiers provide elongation, flexibility, and toughness.

[0069] In a preferred embodiment, the impact modifier of the present invention is a multi-stage, sequentially produced polymer having a core / shell particle structure of at least three layers consisting of a hard core layer, one or more intermediate elastomeric layers, and a hard shell layer. The presence of the hard core layer provides an ideal balance of good impact strength, high modulus, and excellent UV resistance that cannot be achieved with a core / shell modifier having a soft core layer.

[0070] The hard core layer (Tg>0°C, preferably Tg>20°C) is generally a polymer of a single composition, but may also include a combination of a small amount of low Tg seeds (on which the hard core layer is formed). The hard core layer can be selected from any thermoplastic that meets the Tg requirements. Preferably, the hard core layer is mainly composed of methacrylate units, acrylate units, styrene units or a mixture thereof. Preferably, the acrylate units are selected from: methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate and octyl acrylate. Styrene units include styrene and its derivatives, such as but not limited to, α-methylstyrene and p-methylstyrene. In one embodiment, the hard core layer is all acrylic.

[0071] The one or more intermediate layers are elastomers having a Tg of less than 0°C, preferably less than -20°C. Preferred elastomers include polymers and copolymers of alkyl acrylates, dienes, styrenes and mixtures thereof. Preferably, the soft intermediate layer consists essentially of acrylate units. The shell layer may be made of one or more shell layers having a Tg>0°C, more preferably a Tg>20°C. The composition of the shell layer may be the same or different from that of the hard core layer.

[0072] Preferably, the multi-stage polymer is a three-stage composition, wherein each stage is present in the following ranges: 10 wt% to 40 wt%, preferably 10 wt% to 20 wt% of the first stage (a), 40 wt% to 70 wt%, preferably 50 wt% to 60 wt% of the second intermediate stage (b), and 10 wt% to 50 wt%, preferably 20 wt% to 40 wt% of the last stage (c), all percentages based on the total weight of the three-stage polymer particles.

[0073] In one embodiment, the core layer is cross-linked polymethyl methacrylate-ethyl acrylate copolymer, the middle layer is cross-linked polybutyl acrylate-styrene copolymer, and the outer shell is polymethyl methacrylate-ethyl acrylate copolymer.

[0074] Multistage polymers can be produced by any known technique for preparing multistage, sequentially produced polymers, for example, by emulsion polymerization of subsequent stage mixtures of monomers in the presence of previously formed polymer product. In this specification, the term "sequential emulsion polymerization" or "sequential emulsion production" refers to polymers prepared in aqueous dispersions or emulsions, wherein successive monomer loads are polymerized onto or in the presence of a preformed emulsion prepared by polymerization of previous monomer loads and stages. In this type of polymerization, subsequent stages are attached to and intimately associated with prior stages.

[0075] In a preferred embodiment, the refractive index of the core / shell particles matches the overall refractive index of the matrix made of the acrylic polymer composition. Matching means that the refractive index of the core / shell particles should be within 0.03 units, preferably within 0.02 units of the refractive index of the matrix polymer.

[0076] In a preferred embodiment, an impact modifier is selected that has the least effect on increasing the viscosity of the low Tg acrylic composition. High efficiency impact modifiers with high rubber content allow for lower loadings and therefore have less effect on increasing the viscosity of the composition. Block copolymers are self-assembling and have less adverse effect on the viscosity of the composition.

[0077] Acrylic Alloy

[0078] An alternative approach to providing an overall low Tg acrylic composition involves alloy blends of one or more higher Tg acrylic polymers with one or more lower Tg (low melt flow) polymers. This approach is described in WO 2017 / 210,286.

[0079] The low melt viscosity polymer in the acrylic alloy composition must be compatible, semi-miscible or miscible with the acrylic polymer. The low melt viscosity polymer and the acrylic polymer should be able to be blended in a certain proportion to produce a single homogeneous mixture without separation into different bulk phases. As used herein, "low melt viscosity polymer" refers to a polymer having a melt flow rate greater than 10 g / 10 min, preferably greater than 25 g / 10 min, as measured by ASTM D1238 at 230°C / 10.4 kgf.

[0080] In one embodiment, the low melt viscosity polymer is a low molecular weight acrylic polymer or copolymer that meets the high melt flow rate standard. The weight average molecular weight of the low molecular weight acrylic polymer is less than 70,000 g / mol, preferably less than 50,000 g / mol, more preferably less than 45,000 g / mol, and even less than 30,000 g / mol. Acrylic copolymers are preferred, preferably copolymers with Tg below 100°C and below 90°C to improve flexibility.

[0081] In a preferred embodiment, the low melt viscosity polymer of the present invention is a polymer other than an acrylic polymer. The non-acrylic low melt viscosity polymer of the present invention includes, but is not limited to, polyesters, cellulose esters, polyethylene oxides, polyalkylene glycols, polyethylene glycols, polypropylene glycols, polyhydroxyalkanoates, styrene-acrylonitrile copolymers, polyvinyl chloride, polyvinyl acetate, polyvinyl alcohol, ethylene-vinyl acetate copolymers, polyvinylidene fluoride and copolymers thereof, olefin-acrylate copolymers, olefin-acrylate-maleic anhydride copolymers, maleic anhydride-styrene-vinyl acetate copolymers and mixtures thereof.

[0082] Useful polyesters include, but are not limited to, polybutylene terephthalate, polyethylene terephthalate, glycol-modified polyethylene terephthalate, and polylactic acid. The preferred polyester is polylactic acid.

[0083] Useful cellulose esters include, but are not limited to, cellulose acetate, cellulose triacetate, cellulose propionate, cellulose acetate propionate, cellulose acetate butyrate, and cellulose acetate phthalate.

[0084] In one embodiment, the low melt viscosity polymer has a weight average molecular weight that is higher than the entanglement molecular weight of the polymer as measured by gel permeation chromatography.

[0085] The low melt viscosity polymer comprises 5 to 60 wt %, preferably 9 to 40 wt % of the total alloy composition.

[0086] Acrylic blends with non-polymers

[0087] A third method for providing an all-acrylic composition with a lower Tg is to blend a higher Tg acrylic polymer with one or more compounds known to reduce Tg, such as, but not limited to, plasticizers. The additive composition must be compatible, semi-miscible or miscible with the acrylic polymer. The Tg-reducing additive is typically added at 2 to 40 weight percent, preferably 4 to 20 weight percent, based on the weight of the acrylic polymer.

[0088] In one embodiment, a useful class of plasticizers is a specialty epoxide, for example, a 1,2 dihydroxyalkane having a molecular weight greater than 200 grams per mole or a vegetable oil polyol having a molecular weight greater than 200 grams per mole, as described in PCT / US2019 / 012241.

[0089] In another embodiment, phthalic acid esters such as di(2-ethylhexyl)phthalate, diisononyl phthalate, diisodecyl phthalate, and diisooctyl phthalate may be used.

[0090] In another embodiment, adipate esters such as, but not limited to, di(2-ethylhexyl) adipate may be used.

[0091] Viscosity

[0092] The polymer composition of the present invention has a viscosity of 230°C, 1 second, and 100% viscosity as measured by a rotational viscometer according to ASTM C965. -1 The viscosity under shear rate is less than 100000 Pa-s, preferably less than 20000 Pa-s, preferably less than 10000 Pa-s, at a temperature of 230°C and a shear rate of 100 seconds. -1 The viscosity at shear rate is 20 to 2000 Pa-seconds, preferably 25 to 1000 Pa-seconds, more preferably 30 to 500 Pa-seconds. This viscosity is useful for 3D printing compositions and also provides a composition that is sufficiently liquid at internal temperature to allow mixing of polymer chains in adjacent layers.

[0093] Once the composition is printed, the viscosity of the printed dot / line of the amorphous thermoplastic polymer composition is within 1 second for at least 5 minutes, preferably 10 minutes, preferably 15 minutes, preferably 20 minutes and preferably 25 minutes after printing. -1 The viscosity under shear is maintained at less than 200,000 Pa-s, 100,000 Pa-s, 50,000 Pa-s.

[0094] Printing part density

[0095] To most effectively remove small gaps that scatter light, the final part density as measured by ASTM D792 should be at least 95%, preferably 98%, preferably 99% of the polymer volume density. High density is achieved by overfilling the print by 1% to 10%, combined with composition fluidity due to temperature adjustment - providing sufficient time and low enough viscosity to remove any air pockets.

[0096] Another advantage of parts with very high internal density and internal layer line merging is improved mechanical properties in the Z direction. The method of printing internal transparent parts also produces parts that are close to isotropic.

[0097] CEILING HEIGHT

[0098] Layer height, as known in the art, is the Z-direction thickness of the constituent layers when deposited by an extruder in the XY direction. Due to the density of the polymer, the deposited traces within the layer have a cross-section of a geometric stadium (also known as a discord angle). The rounded edges of the polymer traces result in inter-grating and inter-layer gaps, causing light to scatter as it passes through the printed object. In addition, the rounded outer layers act as small lenses, further scattering the light. This light scattering moderately reduces transmittance and significantly increases the haze of the printed article (both measured according to ASTM D1003).

[0099] It has been shown that at very small layer heights (0.05 mm), it is possible to create somewhat crisp parts using FFF printing. Printing at these very small layer heights allows the nozzle to reheat the material and remove any internal voids that would otherwise exist. External part surfaces must be sanded and polished to appear crisp. Unfortunately, the small layers lead to a significant increase in print time, with a simple 10 cm tall object requiring 2000 individual layers. If the object were a simple 1000 cm cube, each layer would take about 20 minutes to print at a print speed of 25 mm / sec, resulting in a final print time of nearly 27 days. The speed at which the layers are deposited cannot be increased without significantly sacrificing fidelity, so thin layer heights will result in unacceptably long print times. As layer heights increase, the crispness of the part decreases dramatically. Through control of the process parameters and modification of the resin rheology, these limitations can be overcome, allowing crisp parts to be printed at layer heights up to 0.4 mm.

[0100] Print speed

[0101] The main parameter for controlling the print head movement rate is generally referred to as print speed. In a preferred embodiment, the print speed is greater than 10 mm / sec, preferably greater than 15 mm / sec, most preferably greater than 20 mm / sec, but preferably less than 55 mm / sec. Improvements beyond this point will not significantly reduce the print time, because the print speed only controls the maximum speed of the nozzle in the XY plane, and the acceleration and jerk of the nozzle are limited. These limitations depend on the printer and its construction. In addition, due to the inertia when the fluid polymer is deposited, extrusion speeds greater than 75 mm / sec are often very imprecise.

[0102] Printer design

[0103] For material extrusion additive manufacturing 3D printing, the printer typically has a heated print bed at 50–150°C (preferably above 60°C, more preferably above 75°C). The printer features one or more heated nozzles through which the material is extruded. These nozzles are typically capable of reaching 200°C (preferably 250°C, more preferably above 300°C). The printer is characterized by a build environment that is open to ambient conditions, or closed. The printer may feature other control functions, such as an actively heated or cooled build environment. The printer may feature radiant heating elements or forced convection heating elements within an open or closed build volume to increase or maintain internal component temperatures.

[0104] The printer may feature a mixing head that allows multiple raw materials to be combined, such as a Diamond Hotend, wherein any raw material combination or the final combination after mixing meets the specifications described herein. In another embodiment, the printer is fed with multiple compositions combined in a direct pellet extruder print head, wherein any composition or the final mixed composition meets the specifications described herein.

[0105] Printing temperature, internal temperature

[0106] Printing temperature or internal temperature as used herein is intended to define the temperature of the printed material composition even after the material composition has passed through the printer nozzle and deposited on the print bed. It is also referred to as the internal temperature, but should not be confused with the nozzle temperature. The printed material will constitute points in the printed layer, and its associated printing temperature will decrease as the material cools. Within a specified time after the material is deposited, the internal temperature is at least 20°C higher than the Tg of the printed composition, more preferably at least 30°C higher, more preferably at least 40°C higher, even at least 50°C higher, even 60°C higher. The internal temperature may be affected by multiple factors, including but not limited to: printer nozzle temperature, print bed temperature, ambient temperature (which can be the ambient temperature or inside a heated chamber), fan or active cooling speed, and any additional radiation or convection energy.

[0107] Nozzle temperature

[0108] The nozzle temperature is easily adjustable. The polymer composition is in contact with the nozzle for only a short time, so the nozzle temperature has little effect on the internal temperature, especially over time. The nozzle temperature is responsible for adding heat to each layer as it is added to the component. The nozzle is typically heated to 170°C to 300°C, preferably 210°C to 240°C. Preferably, the nozzle is set at the upper range of the material processing temperature.

[0109] Print bed temperature

[0110] The print bed helps keep the internal temperature of the print elevated. The effect of a heated print bed on part temperature can be observed 10, 20, 30, or even 40 layers above the print bed as it continues to provide heat to the interior of the print. A heated print bed also helps reduce any warping.

[0111] The print bed should be set above the Tg of the polymer composition, preferably up to 10°C, even 20°C, 25°C, 30°C above the polymer combination Tg. Alternatively, the print bed can be set % higher than the composition Tg, preferably 10%, 20%, 30%, 40% higher than the Tg, as measured in degrees Celsius.

[0112] Higher print bed temperatures unexpectedly had the unintended effect of allowing transparent parts to be printed with thicker individual layers. All previous approaches showed a significant increase in optical haze at thicker layer heights. Setting the heated print bed well above the material T g At temperatures of 100 °C, we were able to print 3.2 mm thick panels with layer heights of 0.2 mm, 0.3 mm, and even 0.4 mm with an internal haze of less than 10% (see Examples 1 and 2).

[0113] The higher print bed temperature and lack of cooling fans / active cooling allows the most recently printed layer to maintain its temperature and mobility within a range of about 6 mm from the topmost layer to the print surface. At a given print speed, this means about 20 minutes before a given layer cools below a temperature that significantly reduces fluidity. The higher internal temperature increases fluidity, allowing the interior of the part to become transparent, while the higher first G' / G" crossover temperature (190°C) means that the material is sufficiently cured to handle more complex geometries. Basically, the material composition selected in accordance with the present invention is able to remain in the transparent processing temperature range for a sufficient time to provide a transparent part while maintaining good part geometry definition.

[0114] Heated chamber

[0115] When a heated chamber is used, the part cools more slowly, experiences higher internal temperatures, and therefore higher Tg materials can be used. The chamber temperature should be selected to be above ambient but below the Tg of the polymer composition. Chamber temperatures greater than 30°C, 40°C, 50°C, and preferably above 60°C or below can be used. However, good internally transparent parts can be 3D printed at ambient temperatures, provided that the Tg of the composition and the print bed temperature are carefully selected.

[0116] Radiant Energy

[0117] In one embodiment, the heat from printing may be supplemented by a radiant energy source such as an infrared heater.

[0118] Component cooling fan

[0119] To increase the internal temperature of the print, the active component cooling system (typically fans) is turned off or disabled during printing. In a preferred embodiment, the system consists of one or more radial or axial fans with variable speed control. In another embodiment, a system can be provided to direct the airflow using a series of valves or ducts to direct the airflow away from the printed article. In another embodiment, the airflow is preheated so that the airflow interacting with the component being printed does not cause significant cooling, and active heating of the component may be performed. Other forms of forced convection heating, rather than cooling, are also contemplated.

[0120] CEILING HEIGHT

[0121] It is well known that reducing the layer print height to 0.05 mm and below can improve the clarity of the printed part. This is primarily due to the constant renewal of heat from the nozzle, which increases the amount of heat added to each printed layer. Unfortunately, the increased printing and heat can also cause polymer degradation and yellow or brown coloration. In the present invention, parts can be printed using layer heights of 0.1 mm, 0.2 mm, 0.3 mm, and even 0.4 mm, while still achieving an internal haze of less than 15%, less than 10%, or even less than 5%.

[0122] time

[0123] A key parameter for achieving excellent clarity in a printed article is a high positive ΔT (printing material temperature minus the material's Tg) maintained for more than 5 minutes, preferably at least 10 minutes, at least 15 minutes, and more preferably at least 20 minutes. This extended time frame at an elevated temperature above the material's Tg provides the polymer chains with time and mobility to mix with adjacent polymer chains, thereby reducing or eliminating any print lines in the article.

[0124] The long Delta T time is provided by a large positive initial Delta T, a packing density close to 100%, and print bed and chamber temperatures to reduce heat dissipation from the part.

[0125] In one embodiment, a phase change material (eg, a phase change polymer) may be added at low levels to help maintain the temperature of the print.

[0126] Material Extrusion Additive Process

[0127] The amorphous thermoplastic polymer compositions of the present invention are used as powders or pellets and, in a preferred embodiment, are formed into filaments, typically by an extrusion process.

[0128] The composition will be 3D printed in a material extrusion (fused deposition molding, fused filament manufacturing) type 3D printer with or without filament (any size diameter, including 1.75 mm, 2.85 mm or other size) at any speed using any size nozzle, and filaments, pellets, powders or other forms of acrylic compositions can be used. The 3D printing of the present invention is not a laser sintering process. For this purpose, the composition can be made into filaments. It may even be nozzle sprayed onto the surface to be printed (spray-melted plastic), for example by Arburg Freeformer technology.

[0129] A general description of the printing process includes the following steps: polymer composition filaments, pellets or powders are fed into a material extrusion printer. The printer's computer controls are set to provide a certain volume of material flow and to space the print lines at a certain distance. The machine feeds the polymer composition into a heated nozzle at a set speed, and the printer moves the nozzle to the appropriate position to deposit a set amount of the polymer composition.

[0130] In a preferred embodiment, the polymer has a low shear viscosity as described above. The printer typically has a heated print bed at 50-150°C (preferably above 60°C, more preferably above 75°C). The printer is characterized by one or more heated nozzles through which the material is extruded. The printer can be characterized as a build environment that is open to external conditions, or closed.

[0131] In a preferred embodiment, the 3D printer is programmed to run at a slight overflow (also called overfill) of 1% to 10%. This means that the volume of the polymer composition fed by the printer is greater than the calculated volume required for the 3D article being formed. The overflow will more tightly wrap the acrylic composition, increase the density of the parts, and at the same time improve the strength, mechanical properties and optical properties of the printed article. The overflow can be set in two different ways. In the first method, the software is set to feed a higher percentage of material to the nozzle than is normally required. In the second method, the software is set to reduce the line spacing, thereby creating overlaps in the lines, resulting in additional material being printed into the article.

[0132] The process parameters of the 3D printer can be adjusted to minimize shrinkage and warping and produce 3D printed parts with optimal strength and elongation. The use of the selected process parameters is applicable to any extrusion / fusion 3D printer, and preferably to filament printing.

[0133] Other process conditions that can improve the construction time of the printed article, produce excellent definition and Z-direction physical properties include: increasing the temperature of the printer's print bed and / or build chamber. It is believed that in order to obtain the best results, the internal temperature of the printed article should be at least 25°C higher than the material Tg (higher than the Tg of the polymer composition), more preferably at least 35°C higher, more preferably at least 45°C higher, more preferably at least 55°C higher, and even 65°C or 75°C higher. In a preferred embodiment, the shell of the printed article needs to be sufficiently rigid, and the cooling rate must be fast enough for some part resolution, while the internal temperature is as high as possible.

[0134] Transparent material extrusion additive process:

[0135] In one embodiment, the 3D printer is programmed to move the extrusion nozzle at a speed slightly slower than the normal printing speed (25 mm / sec) with the part cooling fan turned off to allow the part to retain more heat. The 3D printer is set to extrude very thin layers with a layer height of 0.05 mm. The 3D printer will be run at a slight overflow of 1% to 10% to allow for filling of interlayer gaps. The print bed is set close to or slightly above the material Tg, and the nozzle is set at the upper range of the material processing temperature. We were able to demonstrate that low Tg acrylics can achieve internal transparency when using this approach (with a heated print bed temperature of only 85°C). Surprisingly, when transparency and haze are measured with BYK-Gardner Haze-Gard on a 3.2 mm thick plaque according to ASTM D1003, acrylic materials are the only materials that can achieve haze less than 20%, preferably less than 15%, 10%, and most preferably less than 5%, and transmittance greater than 84%, 86%, 88%, and 89%. This is true even at a layer height of 0.1 mm.

[0136] In another embodiment, the heated print bed temperature can be raised above the material Tg, further slowing the cooling rate of the extruded plastic and allowing it to remain above its liquid-to-solid transition point for a longer period of time. It is believed that raising the build surface temperature far above the Tg of a material would cause it to sag and deform; however, surprisingly, it has been found that the acrylic material of the present invention is able to maintain its shape during printing with a print bed temperature 40°C above the material Tg. Without being bound by any particular theory, it is believed that the acrylic material can be soft but still maintain its shape because there is a large delta (which is called the transparent processing range) between the first G' / G" intersection and the LS transition on the rheological curve discussed herein. In one embodiment, by using an infrared thermal imager, it was shown that the internal part temperature was 50°C above the material Tg, but as the internal temperature dropped below the first intersection, the part maintained its shape. The higher print bed temperature produced improved part transparency. A larger transparent processing range allows the use of higher print bed temperatures without causing the part to lose its shape, so a larger transparent processing range is desired, preferably greater than 40°C, greater than 50°C, greater than 60°C, greater than 70°C, and greater than 80°C.

[0137] The higher print bed temperature had the unexpected effect of eliminating the requirement to print very thin layers / minimize layer heights. Surprisingly, at 25mm / sec, a 3.2mm plate printed at 0.2mm, 0.3mm, and even 0.4mm layer heights had less than 10% haze. 0.3mm and 0.4mm layer heights are typically used for faster, less precise, or very large 3D prints, but using this technique we can produce internally clear parts with minimal layer lines. It takes 8 times longer to produce an object with 0.4mm layers than with 0.05mm layers.

[0138] Application / Use

[0139] Acrylic resins are widely used in applications where beneficial properties are required (clarity, weatherability, etc.) This 3D printable acrylic material can be used in multiple markets, including (but not limited to): automotive, construction, fabrics (capstock), aviation, aerospace, photovoltaics, medical, computer-related products, telecommunications, and wind energy. These applications include (but are not limited to): exterior paneling, automotive body panels, automotive body trim, RV body panels or trim, exterior panels for recreational sporting equipment, marine equipment, exterior panels for outdoor lawn, garden and agricultural equipment, marine exterior paneling, aerospace structures, aircraft, public transportation applications, interior paneling applications, interior automotive trim, headlight components, vehicle taillights, lenses, prototyping, display panels, interior panels for marine equipment, interior panels for aerospace and aircraft, interior panels for public transportation applications, and paneling for appliances, furniture and cabinets, RV, sporting equipment, marine, aerospace, decks, railings, siding, door and window profiles, dishwashers and dryers, refrigerators and freezers, appliance housings or doors, bathtubs, showers, spas, counters, storage facilities, decorative exterior trim, molded side trim, side panel trim, fenders and fender extensions, louvers, rear end panels, pickup truck tonneau covers, mirror housings, accessories for trucks, buses, campers, vans and mass transit vehicles, b-pillar extensions etc.; appliances and tools, such as lawn and garden tools, bathroom fixtures for mobile homes, fences, boat components, exterior components for mobile homes, lawn furniture, lawn chairs, table stands, pipes and pipe end caps, luggage, shower stalls, toilet seats, signs, spas, air conditioning and heat pump components, kitchen utensils, bead molded picnic coolers, picnic trays and water bottles, and trash cans, venetian blind components, sporting goods, windsurfing, sailboats, plumbing components, toilet components, building components, building moldings, door moldings, blinds, shutters shutters, mobile home skirtings, residential or commercial doors, siding accessories, window coverings, storm window frames, skylight frames, gutter end caps, awnings, medical devices, automotive porthole roofs, lamps, lighting equipment, sensors, consumer products, silverware, automotive trim, prototypes, figurines, dentures, hardware, cabinets, ball bearings, hoses, eyeglasses, cages, UV protection screens, windows, signs, toys, medical devices and devices (such as implants) and device components, lighting appliques, luminares, window coverings, surface modifications, 3D model-based visualization aids, medical imaging, architectural models, terrain data, mathematical analysis or other data sets.Teaching aids, props, costumes, park benches, robotic components, electrical closures, 3D printer components, jigs, fixtures, manufacturing aids, molds, sculptures, statues, board games, miniatures, dioramas, trophies, drones, medical devices (Class I, II, and III under 21 CFR), optical waveguides, interior lighting, integrated optical assemblies, display assemblies, instruments, see-through components, solar cells, fixtures and rigging for solar power systems, artificial nails, dosimeters, jewelry, footwear, fabrics, firearm components, cell phone cases, packaging. Example

[0140] Example 1 Internal transparent plate measurement

[0141] 35mm x 35mm plates with a thickness of 3.2mm were 3D printed on an Ultimaker S5 3D printer using various different plastic filaments. The transmittance and haze of each plate were measured using a BYK-Gardner Haze-Gard. The rough surface of the plate results in very high haze values ​​because the ridges scatter light. Instead of manually sanding and polishing the surface, a liquid that roughly matches the refractive index is used to smooth the surface. The 3D printed plate was coated with glycerol (n≈1.45) and then pressed against an acrylic plate and measured. The plate was measured without glycerol, with glycerol on one side, and with glycerol on both sides. A schematic of our test is shown below. Figure 1 These results are listed in Table 1.

[0142] The 15-30% ethyl acrylate modified copolymer was able to achieve the highest transmittance and lowest haze of the material, with the lowest haze measured being 3.5%. Without the modified copolymer to lower the Tg and change the rheology, the mid-Tg PMMA could only achieve a haze of 14% under optimal conditions. The printer used was limited by the print bed temperature that could be achieved and there was no heated chamber, which prevented the internal component temperature from reaching the required temperature of 10°C, 20°C, 30°C above its LS transition point to obtain the mobility required to allow the layer interface to fully merge. Without being bound by any particular theory, it is believed that if the print bed is set hot enough to allow the internal temperature to reach about 160°C, then an impact modified PMMA with a Tg of about 105-110°C can achieve a haze of less than 10%, or even less than / 5%.

[0143] Table 1

[0144]

[0145] Example 2

[0146] Print transparent parts at thicker layer heights

[0147] Impact modified low Tg containing 15-30% low Tg comonomer content g The acrylic composition was used to print optical plaques at different layer heights and a printer speed of 25 mm / sec. These 35 mm x 35 mm x 3.2 mm plaques were tested using the same procedure as described in Example 1. The optical haze for each of these plaques can be seen in Table 2. Plaques printed using 0.05 mm and 0.1 mm layer heights had low haze, but once the layer height was increased to 0.2 mm, the haze increased to 37.9%. This layer height limitation is a significant setback, as 0.2 mm layers are considered standard in the art, and 0.1 mm and 0.05 mm layers double and quadruple the time required to print an object, respectively.

[0148] Table 2

[0149]

[0150] To reduce printing time, the print bed temperature was increased to 120°C while keeping haze low. Surprisingly, the specific rheological properties of the acrylic composition allow it to maintain its shape even when heated above its Tg. The additional mobility of the polymer allows for filling of voids even when printing in thick layers while maintaining dimensional stability. By increasing the print bed temperature from 75°C to 120°C, the haze of the finished part was reduced from 37.9% to 8.6% when printing with a 0.2 mm layer height. Boards printed using 0.3 mm and 0.4 mm layer heights exhibited better performance than those printed using a 0.2 mm layer height. Using a 0.4 mm layer height and a print speed of 25 mm / s, the board was printed in just 22 minutes, but its optical properties were similar to boards that took several hours to produce at lower print bed temperatures and smaller layer heights.

[0151] Table 3

[0152]

[0153] We also tested T g Impact-modified PMMA between 105°C and 110°C (Table 4). Although Example 1 had a slightly lower haze of 14.0% when printed at a 0.05 mm layer height, the material did not print clearly when printed with thicker layer heights. The printer used could only reach a print bed temperature of 120°C, and after 10 to 15 minutes, the internal temperature reached a temperature higher than its T g Without being bound by any particular theory, this level of heat soak is insufficient to allow the material to be printed with low haze at thicker layer heights, but it is believed that if a higher internal temperature can be achieved by a hotter print bed or heated chamber, the acrylic composition can be printed with low haze at layer heights of 0.2 mm or more, such as with low T g Acrylic compositions are shown.

[0154] Table 4

[0155]

[0156] Amphora HT copolyester (Table 5) and standard T g PMMA has the same properties: it is characterized by low haze when printed in 0.05 mm layers, but the level of heat soaking that our printer can achieve is not enough to make the material print clear at thicker layer heights. Due to the lower Tg of this material relative to the mid-Tg PMMA composition g Therefore, as the layer height increases, the haze of AmphoraHT increases more slowly.

[0157] Table 5

[0158]

[0159] PETG was also tested, although its thermal properties are similar to those of low T g The acrylic composition is similar, but due to its low viscosity at elevated temperatures and low shear, the polymer cannot be printed at higher print bed temperatures, specifically, its clear processing window is only 35°C, the G' / G" first crossover temperature is 122°C, and the LS transition temperature is about 87°C. The material sags / flows when printed, and the plate loses its shape. This deformation increases the resulting haze as the fluid polymer empties out the original print volume, leaving internal voids.

[0160] Some polymers with good optical properties, such as polycarbonate, have a Tg range of 100°C to 140°C. While not being bound by any particular theory, it is believed that when the print bed temperature of the printer can be higher than the material Tg, the Tg of the material can be increased. g At 5%, 10%, 15% or 20% higher, these materials can also be printed clearly at thicker layer heights, provided they have the appropriate rheological properties as discussed above.

[0161] Example 3

[0162] Infrared thermal imaging of parts during printing

[0163] A Flir E60 infrared camera recorded images of the printing process of Sample 1 when printing a transparent part using the outlined method, with a print bed temperature of 120° C. These images confirm that the temperature inside the part can be maintained significantly above the Tg of the material while the material is able to retain its shape. Figure 2The thermal image shown shows a part that was 110mm x 20mm and 3mm tall when the image was taken. The print bed was at 120°C and the nozzle was at 245°C. The temperature at the measurement point in the center of the screen was 137°C. The internal temperature of the entire part remained above 130°C, but the part was able to maintain its shape during the 5 hour long print process, after which the final height of the part was 20mm.

[0164] Figure 3 The second infrared image shown shows a part that, when printed, measures 20 mm x 30 mm and is 19 mm high. The final part can be seen in Example 4. Figure 4 and Figure 5 The thermal image shows a heat soak at the top of the part. The higher print bed temperature and the absence of cooling fans allow the most recently printed layers to maintain their temperature and mobility within about 6 mm from the topmost layer to the print surface. At a given print speed, this means about 20 minutes before a given layer cools below 130°C. The higher internal temperature causes increased fluidity, which allows the interior of the part to become transparent, while the higher first crossover temperature (190°C) means the material is fully cured to handle more complex geometries.

[0165] Example 4

[0166] Figure 4 and Figure 5 The block shown was printed with two filaments. The composition of the transparent filament was the same as Sample 1 mentioned in Examples 1 and 2. The inner "A" shape was made using an opaque red ABS filament. The two filaments were extruded together through an Ultimaker S5. The object was printed with a layer thickness of 0.3 mm. The layer ridges can be seen in the ABS letters, but the layer interfaces in the acrylic portion have been eliminated by the above process. The block is clear enough to read the text through its 20 mm width. The block was trimmed using an Edge Finisher Company Model EF-200 finisher to form a flat, clear surface.

[0167] The double extrusion block shows that despite the internal part temperature exceeding the material Tg, the plastic can still be deliberately and precisely placed using this method. Although the plastic remains fluid for a long time, it is thick enough to maintain its position and allow the complex internal geometry to be discerned in the clear acrylic.

[0168] Example 5

[0169] Rheology of the material

[0170] A general description of the developed rheological method consists of the following steps: melt the resin between parallel plates with a narrow gap, the gap being 1.8 mm to 0.5 mm. In the presence of fillers, the gap must be at least 10 times larger than the larger filler particles in the resin. The sample is preferably heated to at least 30°C to 50°C above the melting temperature, but well below the decomposition temperature. The rheometer used in the present invention is the MCR502 from Anton Paar. The software is programmed to shear the sample by applying a small oscillating force while the temperature is reduced at a constant cooling rate (5°C / min to 10°C / min is recommended). The test should always be performed in the linear viscoelastic region, which can be determined by performing a strain amplitude sweep on each resin before the temperature sweep test.

[0171] The rheological properties of low Tg acrylic and high Tg acrylic are as follows Figure 6 and Figure 7 ; Figure 8 and Fig. 9 ; and as shown in Figures 10 and 11. The liquid-solid transition temperature can be obtained from the viscosity curve. The first crossover temperature at which the part begins to exhibit some hardening behavior (where G'>G") is obtained from the modulus.

[0172] In general, the dynamic modulus is a measure of the viscoelastic properties of a material and is the storage modulus G' (i.e., elastic response) and the loss modulus G" (i.e., viscous response) of the polymer. The crossover temperature (G'=G") can be used as the onset of hardening because at lower temperatures, the elastic modulus dominates over the viscous response. In addition, the LS transition temperature can be obtained and the transparent processing range can be calculated.

[0173] Embodiment 6:

[0174] Evaluating the transparency between a lower Tg amorphous polyamide and a higher Tg amorphous polyamide

[0175] Internal transparent plate measurement

[0176] This study evaluated the transparency of parts made from two amorphous polyamides (PA) based on PA11 / aromatic PA copolymers. The goal was to highlight that the ability of a material to be printed as a transparent part is primarily related to its Tg, more specifically, the ability of the 3D printer heating parameters to allow the internal part temperature to be above the material's Tg during printing, and is less dependent on the material's chemistry and its flow rate. For this purpose, the two selected PA materials showed different Tg, as described in Table 6.

[0177] Table 6: Amorphous polyamide data

[0178] Polyamide Tg(℃) MFR (10 g / min, 275°C, 2.16 kg load) PA1 101 8 PA2 150 30

[0179] For this study, 3.2 mm thick 35 mm x 35 mm plates were printed on an Ultimaker S5 3D printer using two PA materials. All printing conditions for solid (100% filled) plates and the resulting transmittance and haze data are summarized in Table 7. The transmittance and haze of each of these plates were measured similarly to Example 1.

[0180]

[0181] Table 7: Printing conditions and transparency measurements

[0182] Under the printing conditions described, parts printed from PA1 showed high transmittance and low haze of 89.1% and 9.25%, respectively. This shows that when the print bed temperature is kept relatively higher than the material Tg (120°C and 101°C, respectively), amorphous thermoplastics with appropriate rheological properties can be printed to produce parts with high transmittance and low haze. When the transparent processing range is 50°C, the first G' / G" crossover temperature of PA1 is 175°C and the LS transition temperature is about 125°C. At the same time, under the most ideal conditions of Experiment 3 (lower layer height helps to retain more heat between layers during printing), although the MFR of the higher Tg PA2 is higher than that of PA1, it can only reach 18.7%.

[0183] IR imaging of different PA materials

[0184] In order to confirm our previous views on the relationship between the internal part temperature during printing and the transparency level of the final PA part, images of the printing process were recorded using a Flir E60 infrared thermal imager (similar to Example 3). For this purpose, a 20*30 mm (X*Y) 20 mm high (Z) solid (100% filling) block was printed on an Ultimaker S.5 printer using each amorphous PA filament according to the printing conditions described in Table 8.

[0185] Table 8: Printing conditions for infrared thermal imaging

[0186]

[0187] Fig.12 The thermal image in shows a PA1 part that was 20 mm x 30 mm and 8 mm high when the image was taken. The temperature at the measurement point in the center of the screen was 134°C. The recorded images show that the high print bed temperature (120°C), high nozzle temperature (280°C) combined with the lack of a cooling fan allow the internal part temperature to be kept above the material Tg (ΔT=33°C) during printing, while still being able to maintain its shape as it prints. These measurements of internal part temperatures are directly related to the good transparency properties of PA1. To confirm the above, thermal images of PA2 parts were also recorded, as shown Fig.13 As shown, it was 8 mm tall when the image was taken. However, although the print bed was raised to 140°C, the internal temperature was only heated to 148°C and did not reach the ΔT above Tg required for printing highly transparent parts. Therefore, even though it shows high flow, the PA2 material cannot achieve the same level of transparency as PA1.

Claims

1. A material extrusion additive manufacturing method, the method comprising the following steps: a) selecting an amorphous thermoplastic polymer composition, the composition comprising a polymer matrix as a continuous phase of the composition, and the composition as a whole having a certain Tg; b) selecting conditions sufficient to provide an internal temperature of the composition when printed, wherein the Tg of the composition as a whole is at least 25°C below the internal temperature; c) melt extrusion printing the amorphous thermoplastic polymer composition to form an article; Wherein, the temperature difference between the Tg of the amorphous thermoplastic polymer composition and the internal temperature of a given printed point or printed line of the thermoplastic polymer composition is maintained for at least 5 minutes after printing.

2. The additive manufacturing method according to claim 1, wherein: The Tg of the composition as a whole is at least 35°C below the internal temperature.

3. The additive manufacturing method according to claim 1, wherein: The Tg of the composition as a whole is at least 45°C below the internal temperature.

4. The additive manufacturing method according to claim 1, wherein: The Tg of the composition as a whole is at least 55°C below the internal temperature.

5. The additive manufacturing method according to claim 1, wherein: The Tg of the composition as a whole is at least 65°C below the internal temperature.

6. The additive manufacturing method according to claim 1, wherein: The Tg of the composition as a whole is at least 75°C below the internal temperature.

7. The additive manufacturing method according to claim 1, wherein: The temperature difference between the Tg of the amorphous thermoplastic polymer composition and the internal temperature of a given printed point or printed line of the thermoplastic polymer composition is maintained for at least 10 minutes after printing.

8. The additive manufacturing method according to claim 1, wherein: The temperature difference between the Tg of the amorphous thermoplastic polymer composition and the internal temperature of a given printed dot or line of the thermoplastic polymer composition is maintained for at least 15 minutes after printing.

9. The additive manufacturing method according to claim 1, wherein: The temperature difference between the Tg of the amorphous thermoplastic polymer composition and the internal temperature of a given printed point or printed line of the thermoplastic polymer composition is maintained for at least 20 minutes after printing.

10. The additive manufacturing method according to claim 1, wherein: Conditions selected to provide the desired internal temperature include one or more of the following: a) selecting a print bed temperature above the Tg of the amorphous thermoplastic polymer composition; b) select a heating chamber temperature of at least 30°C; c) Use radiant heating sources, conductive heating sources or forced convection heating sources to supplement the heat during printing; d) no active cooling; e) using selected additives in the composition to lower the Tg of the composition, or to help the composition maintain the temperature for a longer period of time; f) Use preheated airflow that interacts with the printed part to reduce cooling or reduce the cooling rate, or even actively heat the printed part.

11. The additive manufacturing method according to claim 10, wherein: Selecting conditions to provide the desired internal temperature includes selecting a print bed temperature at least 10°C above the Tg of the amorphous thermoplastic polymer composition.

12. The additive manufacturing method according to claim 10, wherein: Selecting conditions to provide the desired internal temperature includes selecting a print bed temperature at least 20°C above the Tg of the amorphous thermoplastic polymer composition.

13. The additive manufacturing method according to claim 10, wherein: Selecting conditions to provide the desired internal temperature includes selecting a print bed temperature at least 25°C above the Tg of the amorphous thermoplastic polymer composition.

14. The additive manufacturing method according to claim 10, wherein: Selecting conditions to provide the desired internal temperature includes selecting a print bed temperature at least 30°C above the Tg of the amorphous thermoplastic polymer composition.

15. The additive manufacturing method according to claim 10, wherein: Selecting conditions to provide the desired internal temperature includes selecting a heating chamber temperature of at least 40°C.

16. The additive manufacturing method according to claim 10, wherein: Selecting conditions to provide the desired internal temperature includes selecting a heating chamber temperature of at least 50°C.

17. The additive manufacturing method according to claim 10, wherein: Selecting conditions to provide the desired internal temperature includes selecting a heating chamber temperature of at least 60°C.

18. The additive manufacturing method according to claim 10, wherein: The conditions are selected to provide the desired internal temperature including no fan cooling.

19. The additive manufacturing method according to claim 10, wherein: The heating chamber temperature and / or radiant heating varies over time.

20. The additive manufacturing method according to claim 1, wherein: The amorphous thermoplastic polymer composition comprises a polymer selected from the group consisting of (meth)acrylic polymers, copolyester polycarbonates, and amorphous polyamides.

21. The additive manufacturing method of claim 1, wherein: The amorphous thermoplastic polymer composition has a Tg of less than 160°C.

22. The additive manufacturing method according to claim 21, wherein: The amorphous thermoplastic polymer composition has a Tg of less than 150°C.

23. The additive manufacturing method of claim 21, wherein: The amorphous thermoplastic polymer composition has a Tg of less than 140°C.

24. The additive manufacturing method of claim 21, wherein: The amorphous thermoplastic polymer composition has a Tg of less than 130°C.

25. The additive manufacturing method of claim 21, wherein: The amorphous thermoplastic polymer composition has a Tg of less than 114°C.

26. The additive manufacturing method of claim 21, wherein: The amorphous thermoplastic polymer composition has a Tg of less than 105°C.

27. The additive manufacturing method of claim 21, wherein: The amorphous thermoplastic polymer composition has a Tg of less than 95°C.

28. The additive manufacturing method of claim 21, wherein: The amorphous thermoplastic polymer composition has a Tg of less than 90°C.

29. The additive manufacturing method of claim 21, wherein: The amorphous thermoplastic polymer composition has a Tg of less than 85°C.

30. The additive manufacturing method of claim 21, wherein: The amorphous thermoplastic polymer composition has a Tg of less than 80°C.

31. The additive manufacturing method of claim 21, wherein: The amorphous thermoplastic polymer composition has a Tg of less than 75°C.

32. The additive manufacturing method of claim 1, wherein: The amorphous thermoplastic polymer composition is selected from the group consisting of: a) a copolymer having a desired Tg, b) Blends of polymers with a Tg greater than 160°C and low viscosity polymers, c) Blends of polymers having a Tg greater than 160°C and additives capable of lowering the Tg or increasing the working time of the polymer composition.

33. The additive manufacturing method of claim 1, wherein: The composition has a viscosity of less than 100,000 Pa·s at 230° C. and a shear rate of 1 s-1, and a viscosity of 20 to 2000 Pa·s at 230° C. and a shear rate of 100 s-1, as measured by a rotational viscometer according to ASTM C965.

34. The additive manufacturing method of claim 33, wherein: The composition has a viscosity of less than 10,000 Pa·s at a temperature of 230° C. and a shear rate of 1 s −1 as measured by a rotational viscometer according to ASTM C965.

35. The additive manufacturing method of claim 33, wherein: The composition has a viscosity of 25 to 1000 Pa·s at a temperature of 230° C. and a shear rate of 100 s −1 as measured by a rotational viscometer according to ASTM C965.

36. The additive manufacturing method of claim 33, wherein: The composition has a viscosity of 30 to 500 Pa·s at a temperature of 230° C. and a shear rate of 100 s −1 as measured by a rotational viscometer according to ASTM C965.

37. The additive manufacturing method of claim 1, wherein: The composition has a clear processing range of greater than 40°C, the clear processing range being defined by the difference between the LS transition temperature and the first crossover temperature measured by a rheological method.

38. The additive manufacturing method of claim 37, wherein: The composition has a clear processing range of greater than 50°C.

39. The additive manufacturing method of claim 37, wherein: The composition has a clear processing range of greater than 60°C.

40. The additive manufacturing method of claim 37, wherein: The composition has a clear processing range of greater than 70°C.

41. The additive manufacturing method of claim 37, wherein: The composition has a clear processing range of greater than 80°C.

42. The additive manufacturing method of claim 1, wherein: The amorphous thermoplastic polymer composition further comprises 5 to 60 wt % of an impact modifier, based on the total weight of the composition.

43. The additive manufacturing method of claim 42, wherein: The amorphous thermoplastic polymer composition further comprises 10 to 35 wt % of an impact modifier, based on the total weight of the composition.

44. The additive manufacturing method of claim 42, wherein: The amorphous thermoplastic polymer composition further comprises 15 to 30 wt % of an impact modifier, based on the total weight of the composition.

45. The additive manufacturing method of claim 1, wherein: The temperature of the amorphous thermoplastic polymer composition is provided and / or maintained by one or more means selected from the group consisting of: a) a low speed fan or no active cooling, b) a heated print bed, c) a heated chamber, and d) a radiant heat source.

46. ​​The additive manufacturing method of claim 1, wherein: The article comprises the amorphous thermoplastic polymer composition and has a density of at least 95% of the bulk density of the polymer as measured by ASTM D792.

47. The additive manufacturing method of claim 46, wherein: The article comprises the amorphous thermoplastic polymer composition and has a density of at least 97% of the bulk density of the polymer as measured by ASTM D792.

48. The additive manufacturing method of claim 46, wherein: The article comprises the amorphous thermoplastic polymer composition and has a density of at least 98% of the bulk density of the polymer as measured by ASTM D792.

49. The additive manufacturing method of claim 46, wherein: The article comprises the amorphous thermoplastic polymer composition and has a density of at least 99% of the bulk density of the polymer as measured by ASTM D792.

50. The additive manufacturing method of claim 1, wherein: The amorphous thermoplastic polymer composition comprises an acrylic polymer.

51. The additive manufacturing method of claim 1, wherein: The amorphous thermoplastic polymer composition is printed at a layer height of ≥ 0.05 mm.

52. The additive manufacturing method of claim 51, wherein: The amorphous thermoplastic polymer composition is printed at a layer height of ≥ 0.1 mm.

53. The additive manufacturing method of claim 51, wherein: The amorphous thermoplastic polymer composition is printed at a layer height of ≥ 0.2 mm.

54. The additive manufacturing method of claim 51, wherein: The amorphous thermoplastic polymer composition is printed at a layer height of ≥ 0.3 mm.

55. The additive manufacturing method of claim 51, wherein: The amorphous thermoplastic polymer composition is printed at a layer height of ≥ 0.4 mm.

56. A 3D printed product with a clear interior manufactured by the material extrusion additive manufacturing method of claim 1, wherein: The article comprises an amorphous thermoplastic polymer composition, has a printed layer thickness greater than 0.2 mm, and has an internal haze of less than 25%.

57. The 3D printed article of claim 56, wherein: The printing layer thickness is greater than or equal to 0.3 mm.

58. The 3D printed article of claim 56, wherein: The printing layer thickness is greater than or equal to 0.4 mm.

59. The 3D printed article of claim 56, wherein: The internal haze is less than 20%.

60. The 3D printed article of claim 56, wherein: The internal haze is less than 10%.

61. The 3D printed article of claim 56, wherein: The internal haze is less than 5%.

62. The 3D printed article of claim 56, wherein: The amorphous thermoplastic polymer composition comprises an acrylic polymer, a copolyester, a polycarbonate or an amorphous polyamide.

63. The 3D printed article of claim 56, wherein: (1) the article is clear and capable of producing a 3D printed part having a thickness of 2 mm, a total white light transmittance greater than 80% and a haze less than 80% as measured in accordance with ASTM D1003, and (2) the composition is clear and has an internal haze of less than 25% for a 3D printed part having a thickness of 2 mm printed at a line height of 0.1 mm or greater.

64. The 3D printed article of claim 63, wherein: The total white light transmittance is greater than 84%.

65. The 3D printed article of claim 63, wherein: The total white light transmittance is greater than 86%.

66. The 3D printed article of claim 63, wherein: The total white light transmittance is greater than 88%.

67. The 3D printed article of claim 63, wherein: The haze described in (1) is less than 70%.

68. The 3D printed article of claim 63, wherein: The haze described in (1) is less than 60%.

69. The 3D printed article of claim 63, wherein: The line height is 0.2 mm or greater.

70. The 3D printed article of claim 63, wherein: The line height is 0.3 mm or greater.

71. The 3D printed article of claim 63, wherein: The line height is 0.4 mm or greater.

72. The 3D printed article of claim 63, wherein: The internal haze described in (2) is less than 20%.

73. The 3D printed article of claim 63, wherein: The internal haze described in (2) is less than 15%.

74. The 3D printed article of claim 63, wherein: The internal haze described in (2) is less than 10%.

75. The 3D printed article of claim 63, wherein: The internal haze described in (2) is less than 5%.

Citation Information

Patent Citations

  • Dimensionally stable acrylic alloy for 3-d printing

    WO2017210286A1

  • Core-shell filament for printing smooth FDM 3D items

    WO2018162268A1